Biodiversity assessment of flora and fauna in Bukit Panchor Forest Reserve: conservation implications based on IUCN status - Yap, Chee Kong; Wan Solahudin, Wan Mohd Syazwan; Nulit, Rosimah; Abu Bakar, Noraini; Setyawan, A. D.; Ismail, M. S.; Hadir, M. I. M.; Leow, C.S.; Aguol, K. A. (Northeastern University, 2024)
Lowland tropical rainforests, renowned for their rich species diversity, are predominant across Malaysia but increasingly face threats from human activities. This study, conducted on 8 April 2024 at the Bukit Panchor Forest Reserve (BPFR), aimed to assess the impact of nearby rural settlements, recreational areas, and private agricultural lands on the reserve’s native flora and fauna. Using comprehensive landscape surveys, field observations, photographic documentation, and digital tools, we documented species distribution across various taxonomic groups and evaluated their conservation status according to the International Union for Conservation of Nature (IUCN). A total of 20 species were identified, including birds, amphibians, reptiles, mammals, insects, and angiosperms. Most species were classified as Least Concern, though two species—Ratufa bicolor (Near Threatened) and Dryobalanops aromatica (Vulnerable)—require conservation attention. Avian species exhibited the greatest diversity with four species, including Nisaetus cirrhatus limnaeetus and Lonchura striata subsquamicollis, both categorized as Least Concern. Amphibians and reptiles were represented by two species each, including Chalcorana labialis and Eutropis multifasciata. Insect biodiversity was substantial, with five species documented, contributing to the ecological health of the reserve. Furthermore, five angiosperm species were identified, notably Gmelina arborea and the vulnerable Dryobalanops aromatica. These findings underscore the ecological significance of BPFR and highlight the necessity of sustained conservation efforts to safeguard its biodiversity, particularly for species facing higher risk.